Measuring Innovation in China: Construction of a Fundamental Index - Edgar Samid Limón-Villegas; Juan González García (RAN)
Purpose: To construct a fundamental index that captures the role of innovation as a driver of economic growth, going beyond the limitations of traditional production factors. The guiding research question is: Is it possible to build an integrated and statistically robust index to measure China's innovation system? China is selected as a case study due to its remarkable capacity for innovation and adaptation. Methodology: A quantitative approach using multifactorial statistics was applied. Data were obtained from the World Bank, the National Bureau of Statistics of China, and other official sources. Factor analysis techniques, variable standardization, the KMO sampling adequacy test, principal components, and maximum likelihood estimation were used. These tools enabled the reduction of 28 innovation-related variables into two factors that compose the proposed index. Results: The constructed index demonstrates the role of innovation in sustaining China's economic growth. The two extracted factors robustly summarize the key dimensions underlying this phenomenon and directly address the guiding research question. Implications: The findings offer a better understanding of the strategic role of innovation in emerging economies and serve as useful tool for assessing adaptability to change. Furthermore, the index could be applied to other national contexts, constitute the basis for innovation-oriented public policies, and stimulate further research on innovation-based competitiveness. Originality: This study incorporates often-excluded indicators - such as foreign direct investment and gross capital formation - thereby addressing a gap in the literature related to the comprehensive and statistically robust measurement of innovation systems.